Low doses of glyphosate can affect the nutrient composition of common beans depending on the sowing season - Pacheco de Almeida Prado Bortolheiro, Fernanda [UNESP]; de Almeida Silva, Marcelo [UNESP] (Elsevier, 2021)
Glyphosate application, even in low doses, changes the nutrient composition of crops. The objective of this research was to evaluate the effects of low doses of glyphosate and the sowing season on the macronutrient and micronutrient contents of early cycle common beans. Two experiments were conducted in the field, namely one in the winter season and one in the wet season, using the early cycle common bean cultivar IAC Imperador. The experimental design was a randomized complete block design consisting of the application of low doses of glyphosate [0.0, 1.8, 7.2, 12.0, 36.0, 54.0, and 108.0 g acid equivalent (a.e.) ha−1] in the phenological stage V4 with four replications. Environmental conditions, such as air temperature, interfered with the response of early cycle common beans to low doses of glyphosate. In the winter season, doses of 7.2 g a.e. ha−1 and 36.0 g a.e. ha−1 increased the nutrient composition in the bean leaves, whereas only the Cu content increased in the grains by the dose of 1.8 g a.e. ha−1. In the wet season, there was no increase in the nutrient composition in the bean leaves. The Cu, Zn, Mn, and Fe contents in the grains increased with from the dose of 12 g a.e. ha−1 to above the amount normally observed in common beans, thereby improving the nutritional quality of the food. Our study indicated that low doses of glyphosate alter the nutrient composition of common beans, whereas environmental conditions interfere with the response of common beans to low doses of glyphosate.
Keywords: Early cycle cultivar; Hormesis; Macronutrients; Micronutrients; Phaseolus vulgaris L.